KARAKTERISTIK SIMPLISIA TEH HITAM DARI TANAMAN Camelia sinensis Var. assamica DARI PERKEBUNAN TEH BALI CAHAYA AMERTA, DESA ANGSERI, KECAMATAN BATURITI, KABUPATEN TABANAN, BALI - N. L. P. V. Paramita; N. M. D. Andani; I. A. P. Y. Putri; N. K. S. Indriyani; N. M. P. Susanti (Jurnal Kimia (Journal of Chemistry), 2019)
Black tea is a type of tea in such a way the polyphenols undergo a high degree of oxidation. The characteristics of simplicia are strongly influenced by the environment. In order to use a simplicia as an active ingredient, characterization test are required for maintaining the quality and safety. This study aimed to find out the characteristic of black tea simplicia from tea leaves (Camellia sinensis var. assamica) which were taken from Bali Cahaya Amerta Tea Plantation, Angseri Village, Baturiti Sub-district, Tabanan Regency, Bali. The characterization of the simplicia was done based on standard parameters of tea plant in Farmakope Herbal Indonesia including macroscopic test, microscopic test, the loss on drying, the contents of water soluble compound, ethanol soluble compound, total ash, acid insoluble ash, total phenol and the identification of cathecin. The results showed that black tea simplicia elongated shaped with blackish brown, odorless, tasteless, and there were fragments identifier such as sclerenkim fibers, epidermis with stomata, macrosklerida, leaf mesophyll with vascular tissue, and rosette calcium oxalate crystals. The result of the compounds content that dissolve in water was 31.84% ± 0.6446%, compounds content that dissolve in ethanol was 16.64% ± 0.414%, the loss on drying was 5.19% ± 0.0902%, total ash content was 4.67% ± 0.0392%, ash content that was insoluble in acid was 0.19% ± 0.0025%, and the total fenol content was 0.9733% ± 0.0189%. From the results, the black tea simplicia fulfills the requirements of simplicia characteristic based on Farmakope Herbal Indonesia parameter.